If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + 7q = 46 Solving 2p + 7q = 46 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-7q' to each side of the equation. 2p + 7q + -7q = 46 + -7q Combine like terms: 7q + -7q = 0 2p + 0 = 46 + -7q 2p = 46 + -7q Divide each side by '2'. p = 23 + -3.5q Simplifying p = 23 + -3.5q
| 20yx=10-5yx | | 5y-11y= | | (x-12)+(16-2x)= | | 15yx=5-10yx | | -12(x-12)=-9(1+7) | | 5x+5=7+x | | 10x-17y= | | 13b=7-16b | | 3(w-2)=11 | | 2F=18 | | -16x=2-4x | | (4x+12)-8=(12+3x)-8 | | 9x+6y+2=0 | | 3(2q-7)-(3q-8)=22 | | 4x^2-27x+23=-4x+8 | | x+(x+4)=3+(x+1) | | 6x+14=23-3x | | 10x=51-7x | | -14x=7-9x | | x^2-9x-3=-8x-1 | | 3x+4=58-3x | | x^2+4x-28=4 | | 3x+9=79-7x | | -14x=7-9 | | Damn=you | | 10x=90-5x | | 4(3w+5)-30=7w | | 4x+10=40-2x | | x^2+3x-13=2x-1 | | 6x=15+3x | | x^2-2x-4=4 | | 5x+6-1=18+4x-6 |